Potential for organ donation in the United Kingdom: audit of intensive care records. Issue 7550 (26th April 2006) - Barber, Kerri; Falvey, Sue; Hamilton, Claire; Collett, Dave; Rudge, Chris
Abstract: Objectives To determine the true potential for solid organ donation from deceased heartbeating donors and the reasons for non-donation from potential donors. Design An audit of all deaths in intensive care units, 1 April 2003 to 31 March 2005. The study was hierarchic, in that information was sought on whether or not brain stem testing was carried out; if so, whether or not organ donation was considered; if so whether or not the next of kin were approached; if so, whether or not consent was given; if so, whether or not organ donation took place. Setting 341 intensive care units in 284 hospitals in the United Kingdom. Participants 46 801 dead patients, leading to 2740 potential heartbeating solid organ donors and 1244 actual donors. Main outcome measures Proportion of potential deceased heartbeating donors considered for organ donation, proportion of families who denied consent, and proportion of potential donors who became organ donors. Results Over the two years of the study, 41% of the families of potential donors denied consent. The refusal rate for families of potential donors from ethnic minorities was twice that for white potential donors, but the age and sex of the potential donor did not affect the refusal rate. In 15% of families of potential donors there was no record of the next of kin being approached for permission for organ donation. Conclusions Intensive care units are extremely good in considering possible organ donation from suitable patients. The biggest obstacle to improving the organ donation rate is the high proportion of relatives who deny consent.